Oct1/Pou2f1 is selectively required for colon regeneration and regulates colon malignancy. - Karina Vázquez-Arreguín; Claire Bensard; John C Schell; Eric Swanson; Xinjian Chen; Jared Rutter; Dean Tantin (PLoS Genetics)
The transcription factor Oct1/Pou2f1 promotes poised gene expression states, mitotic stability, glycolytic metabolism and other characteristics of stem cell potency. To determine the effect of Oct1 loss on stem cell maintenance and malignancy, we deleted Oct1 in two different mouse gut stem cell compartments. Oct1 deletion preserved homeostasis in vivo and the ability to establish organoids in vitro, but blocked the ability to recover from treatment with dextran sodium sulfate, and the ability to maintain organoids after passage. In a chemical model of colon cancer, loss of Oct1 in the colon severely restricted tumorigenicity. In contrast, loss of one or both Oct1 alleles progressively increased tumor burden in a colon cancer model driven by loss-of-heterozygosity of the tumor suppressor gene Apc. The different outcomes are consistent with prior findings that Oct1 promotes mitotic stability, and consistent with differentially expressed genes between the two models. Oct1 ChIPseq using HCT116 colon carcinoma cells identifies target genes associated with mitotic stability, metabolism, stress response and malignancy. This set of gene targets overlaps significantly with genes differentially expressed in the two tumor models. These results reveal that Oct1 is selectively required for recovery after colon damage, and that Oct1 has potent effects in colon malignancy, with outcome (pro-oncogenic or tumor suppressive) dictated by tumor etiology.